Isolation and Characterization of Phytoconstituents from Casuarina equisetifolia (Casuarinaceae) - Aher, A.N.; Pal, S.C.; Yadav, S.K.; Patil, U.K.; Bhattacharya, S. (Asian Journal of Chemistry, 2010)
The methanolic extracts of bark, wood, leaf and fruits of Casuarina equisetifolia were studied for isolation of tannins and flavonoids by thin layer chromatography (TLC), column chromatography and preparative-thin layer chromatography (P-TLC) and characterized by spectroscopic techniques (UV-visible spectroscopy, infrared spectroscopy, 1H and 13C NMR spectroscopy and mass spectrometry). The tannins (catechin, ellagic acid and gallic acid) were isolated from bark and flavonoid (quercetin) and lupeol from leaf and fruit, respectively and identified with help of preliminary phytochemical methods, physical properties, spectroscopic data and Co-TLC with authentic standards.